THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT AND WORKLOAD ON EMPLOYEE PRODUCTIVITY AT PERUMDA TIRTAULI PEMATANG SIANTAR CITY - Gulo, Vincent Immanuel; Sihombing, Marlon (Transpublika Publisher, 2024)
This study delves into the critical aspects of fostering high productivity levels among employees, a paramount goal for any organization aspiring to achieve profitability. The primary focus is on assessing the impact of perceived organizational support and workload on employee productivity within the context of Perumda Tirtauli in Pematang Siantar city. The research seeks to provide a comprehensive analysis, examining the individual and collective influences of perceived organizational support and workload on the optimal functioning of employees. Employing a quantitative research approach with an associative orientation, this study carefully investigates the relationship between perceived organizational support, workload, and employee work productivity. The research methodology involves the selection of a representative sample of 80 respondents through simple random sampling techniques. By adopting a rigorous quantitative framework, the study aims to quantify and qualify the extent to which perceived organizational support and workload impact employee productivity. The findings of this research reveal compelling insights. Both perceived organizational support and workload exhibit a significant positive influence on employee work productivity, a phenomenon observed both in partial and simultaneous analyses. These results underscore the importance of organizational support and effective workload management in enhancing the overall productivity of employees. As organizations strive for success, recognizing and addressing these key factors can contribute significantly to achieving optimal employee performance and, consequently, organizational success.